Use of the neotropical fish Cnesterodon decemmaculatus for long-term control of Culex pipiens L. in Argentina - Tranchida, Maria Cecilia (2010)
We released the native mosquito fish, Cnesterodon decemmaculatus, into suburban 37 drainage ditches to evaluate its potential as a long-acting agent for the control of CulexCnesterodon decemmaculatus, into suburban 37 drainage ditches to evaluate its potential as a long-acting agent for the control of CulexCulex 38 pipiens larvae in natural breeding sites. The inoculation of predatory fish was conducted in 9 ditches at three densities: 1, 7, and 13 fish/m2 39 during a 2-year period (2006—2008). 40 The number of immature stages of Cx. pipiens was recorded before and after release. On 41 a monthly basis, the digestive-tract contents of some fish and the average number of 42 offspring from the females was recorded. Fifteen weeks after release, a 99% reduction 43 in the number of immature mosquito stages was recorded in the drainage ditches containing 13 fish/m244 , while at 22 weeks, a 99% reduction was also observed in those with 7 fish/m2. The ditches with 1 fish/m2 45 had lower densities of immature mosquito 46 stages relative to the controls, but over the entire experiment these observations did not 47 prove statistically significant. The number of offspring per adult C. decemmaculatuspipiens larvae in natural breeding sites. The inoculation of predatory fish was conducted in 9 ditches at three densities: 1, 7, and 13 fish/m2 39 during a 2-year period (2006—2008). 40 The number of immature stages of Cx. pipiens was recorded before and after release. On 41 a monthly basis, the digestive-tract contents of some fish and the average number of 42 offspring from the females was recorded. Fifteen weeks after release, a 99% reduction 43 in the number of immature mosquito stages was recorded in the drainage ditches containing 13 fish/m244 , while at 22 weeks, a 99% reduction was also observed in those with 7 fish/m2. The ditches with 1 fish/m2 45 had lower densities of immature mosquito 46 stages relative to the controls, but over the entire experiment these observations did not 47 prove statistically significant. The number of offspring per adult C. decemmaculatus2 39 during a 2-year period (2006—2008). 40 The number of immature stages of Cx. pipiens was recorded before and after release. On 41 a monthly basis, the digestive-tract contents of some fish and the average number of 42 offspring from the females was recorded. Fifteen weeks after release, a 99% reduction 43 in the number of immature mosquito stages was recorded in the drainage ditches containing 13 fish/m244 , while at 22 weeks, a 99% reduction was also observed in those with 7 fish/m2. The ditches with 1 fish/m2 45 had lower densities of immature mosquito 46 stages relative to the controls, but over the entire experiment these observations did not 47 prove statistically significant. The number of offspring per adult C. decemmaculatusCx. pipiens was recorded before and after release. On 41 a monthly basis, the digestive-tract contents of some fish and the average number of 42 offspring from the females was recorded. Fifteen weeks after release, a 99% reduction 43 in the number of immature mosquito stages was recorded in the drainage ditches containing 13 fish/m244 , while at 22 weeks, a 99% reduction was also observed in those with 7 fish/m2. The ditches with 1 fish/m2 45 had lower densities of immature mosquito 46 stages relative to the controls, but over the entire experiment these observations did not 47 prove statistically significant. The number of offspring per adult C. decemmaculatus244 , while at 22 weeks, a 99% reduction was also observed in those with 7 fish/m2. The ditches with 1 fish/m2 45 had lower densities of immature mosquito 46 stages relative to the controls, but over the entire experiment these observations did not 47 prove statistically significant. The number of offspring per adult C. decemmaculatus2. The ditches with 1 fish/m2 45 had lower densities of immature mosquito 46 stages relative to the controls, but over the entire experiment these observations did not 47 prove statistically significant. The number of offspring per adult C. decemmaculatusC. decemmaculatus 48 female ranged from 4 ± 1.4 (mean ± SD) to 7.4 ± 0.9. Larval remains were detect.